Protocol for perfusing human axillary lymph nodes ex vivo to study structure and function in real time - Amy Llewellyn; Rachel Barrow-McGee; Julia Stevenson; Jasmine Gore; Kalnisha Naidoo (STAR Protocols)
Summary: Lymph nodes regulate immunity and maintain fluid balance in health and disease. Here, we present a protocol that uses normothermic perfusion to sustain patient-derived lymph nodes ex vivo for up to 24 h to study their structure and function. We describe steps for setting up both thermoregulatory and perfusion circuits, cannulating human lymph nodes, and perfusion. This protocol can be used to study how human lymph nodes change in cancer and other diseases, and/or in response to perturbations, including drugs.For complete details on the use and execution of this protocol, please refer to Barrow-McGee et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.